A scoping review of the changing landscape of geriatric medicine in undergraduate medical education: curricula, topics and teaching methods - Masud, Tahir; Ogliari, Giulia; Lunt, Eleanor; Blundell, Adrian; Gordon, Adam Lee; Roller-Wirnsberger, Regina; Vassallo, Michael; Mari, Daniela; Kotsani, Marina; Singler, Katrin; Romero-Ortuno, Roman; Cruz-Jentoft, Alfonso J.; et al. (European Geriatric Medicine, 2022)
Aim: This scoping review aims to summarise recent developments in Geriatric Medicine that will potentially inform the updating of undergraduate medical curricula for geriatric content. Findings: Based on the thematic analysis of 367 records out of 2503 identified records, we summarised findings across six major themes: curriculum; topics; teaching methods; teaching settings; medical students’ skills and medical students’ attitudes. Message: This review could inform future shaping of undergraduate medical curricula for geriatric content, through model curricula, expansion of geriatric topics and use of various teaching methods and settings. Purpose: The world’s population is ageing. Therefore, every doctor should receive geriatric medicine training during their undergraduate education. This review aims to summarise recent developments in geriatric medicine that will potentially inform developments and updating of undergraduate medical curricula for geriatric content. Methods: We systematically searched the electronic databases Ovid Medline, Ovid Embase and Pubmed, from 1st January 2009 to 18th May 2021. We included studies related to (1) undergraduate medical students and (2) geriatric medicine or ageing or older adults and (3) curriculum or curriculum topics or learning objectives or competencies or teaching methods or students’ attitudes and (4) published in a scientific journal. No language restrictions were applied. Results: We identified 2503 records and assessed the full texts of 393 records for eligibility with 367 records included in the thematic analysis. Six major themes emerged: curriculum, topics, teaching methods, teaching settings, medical students’ skills and medical students’ attitudes. New curricula focussed on minimum Geriatrics Competencies, Geriatric Psychiatry and Comprehensive Geriatric Assessment; vertical integration of Geriatric Medicine into the curriculum has been advocated. Emerging or evolving topics included delirium, pharmacotherapeutics, healthy ageing and health promotion, and Telemedicine. Teaching methods emphasised interprofessional education, senior mentor programmes and intergenerational contact, student journaling and reflective writing, simulation, clinical placements and e-learning. Nursing homes featured among new teaching settings. Communication skills, empathy and professionalism were highlighted as essential skills for interacting with older adults. Conclusion: We recommend that future undergraduate medical curricula in Geriatric Medicine should take into account recent developments described in this paper. In addition to including newly emerged topics and advances in existing topics, different teaching settings and methods should also be considered. Employing vertical integration throughout the undergraduate course can usefully supplement learning achieved in a dedicated Geriatric Medicine undergraduate course. Interprofessional education can improve understanding of the roles of other professionals and improve team-working skills. A focus on improving communication skills and empathy should particularly enable better interaction with older patients. Embedding expected levels of Geriatric competencies should ensure that medical students have acquired the skills necessary to effectively treat older patients.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Curriculum; Geriatric medicine; Geriatric psychiatry; Teaching methods; Undergraduate medical education